Here be Monsters Sylvie Guillem and Akram Khan reviewed. - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Review of Sylvie Guillem and Akram Khan's Sacred Monsters. PALABRAS CLAVE: Sacred Monsters, Akram Khan, Sylvie Guillem, words and dance.